Estimation of phenotypic and path correlation coefficients of yield and some yield components in Tomato (Lycopersicom esculentum Mill.) lines. - خوجه, حسان; مرعي, عبد المحسن; عزو, علي (Latakia University Journal -Biological Sciences Series, 2020)
The research was conducted at Al-Jammaseh station - Agricultural Research Center in Tartous- Syria, to study the phenotypic correlation and path coefficient of yield and some correlated traits, i.e. number of days until start of flowering, number of flowers per cluster, number of fruits per cluster, fruit weight, pericarp thickness, number of locules per fruit, fruit diameter, fruit length,. Seventeen lines were evaluated in 2018 season in three replication using R.C.B.D design. Results of phenotypic correlation showed that yield per plant was positively and significantly correlated with the number of days until the start of flowering (+0.59), fruit weight (+0.67), fruit length (+0.37), fruit diameter (+0.66), number of locules per fruit (+0.28), pericarp thickness (+0.77), but it was negatively and significantly correlated with number of flowers per cluster (-0.41), number of fruits per cluster (-0.42). Path coefficient analysis showed that pericarp thickness, fruit weight and fruit diameter were the most contributed traits in yield variation, therefore, it could be concluded that yield improvement could be achieved by selection for these traits.